Single inhaler triple therapy in COPD – all that glitters is not gold - Deshmukh, Kartik; Khanna, Arjun (Monaldi Archives for Chest Disease, 2021)
Dear Editor, The recent studies on combination triple therapy of inhaled corticosteroid, long acting beta2 agonist and long-acting muscarinic antagonist (ICS-LABA-LAMA) in COPD have consistently demonstrated an improvement in exacerbation frequency and/or improvement of lung function...